# Rationalize the Denominator of sqrt{(2x)/(3c⁴)}

Rationalize the Denominator of the square root of a fraction

Rationalizing the denominator is equivalent to saying: change the number in the denominator from an irrational number (in this case a square root) to a rational number (a number without a fractional exponent).

Rationalize the denominator of √{(2x)/(3c⁴)}

### Comments for Rationalize the Denominator of sqrt{(2x)/(3c⁴)}

 Sep 24, 2012 Rationalize the Denominator by: Staff Answer:Part I√{(2x) / (3c⁴)}= {√(2x) / √(3c⁴)}Rationalizing the denominator means removing the square root sign √ from the denominator (so that the denominator becomes a rational number).To accomplish this, multiply the denominator √(3c⁴)by itself √(3c⁴). √(3c⁴)*√(3c⁴)= √(3*3*c⁴*c⁴)= 3*c⁴= 3c⁴However, in order to preserve the value of the original fraction, both the numerator and denominator must each be multiplied by the same amount: √(3c⁴).To apply this concept, multiply the original fraction by {√(3c⁴)/√(3c⁴)}. The fraction {√(3c⁴)/√(3c⁴)} is equal to 1, so the original fraction is merely being multiplied by 1. As you can see by the following illustration, the value of the original fraction has not been changed.= [original fraction]= [original fraction] * {√(3c⁴)/√(3c⁴)}= [original fraction] * 1= [original fraction]Therefore,= [original fraction] * 1           √(2x) = --------------------------- * 1           √(3c⁴)            √(2x)                          √(3c⁴)= --------------------------- * ------------------           √(3c⁴)                         √(3c⁴)---------------------------------------------------

 Sep 24, 2012 Rationalize the Denominator by: Staff --------------------------------------------------- Part II Multiply both numerators and multiply both denominators, just as you would when multiplying any two fractions:        √(2x) * √(3c⁴) = ---------------------------       √(3c⁴) * √(3c⁴)        √(2x) * √(3c⁴) = ---------------------------              (3c⁴)        √(2x) * c²√(3) = ---------------------------              (3c⁴) Cancel the exponents for the variable “c” to the extent that you can        √(2x) * c²⁻²√(3) = ---------------------------              (3c⁴⁻²)        √(2x) * c⁰√(3) = ---------------------------              (3c²)        √(2x) * 1√(3) = ---------------------------              (3c²)        √(2x) * √(3) = ---------------------------              (3c²)             √(6x) = ---------------------------              (3c²) Final Answer:                  = {√(6x) / (3c²)} Thanks for writing. Staff www.solving-math-problems.com